2018
DOI: 10.26822/iejee.2018336197
|View full text |Cite
|
Sign up to set email alerts
|

Counselors and Special Educators in Rural Schools Working Together to Create a Positive School Community

Abstract: a AbstractSchool counselors and special educators in rural areas working together can be a powerful team to help schools create a positive school community. In one rural school community, they partnered with faculty and staff to implement a School Wide Positive Behavior support program to improve student outcomes. The counselor and special educator, through intentional communication and collaboration, helped develop a positive school community, using the skills and training of their individual disciplines. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…More specifically, rural children typically come from a lower socio-economic background, which is associated with having a lower parental-education level, lower income, and consequently, limited resources for obtaining adequate nutrition, and for having stimulating didactic materials in their homes, as well as not being able to afford enrichment activities (sport, music, dance). Almost all of these disadvantage factors are considered to be associated with lower academic performance (Crane, 1996;LeFevre et al, 2009;Davis-Kean, 2005;Dooley, 2011, McNamara & Kendeou, 2011Thornton, 2018). Consistent with this finding, Mullis and colleagues (Mullis et al, 2012) reported that a location of school (urban vs. rural) had a substantial impact on students' overall low mathematics achievement in the developing countries which are in close distance with Kosovo such as, Macedonia, Croatia, Romania, Turkey, etc.…”
Section: Discussionmentioning
confidence: 90%
“…More specifically, rural children typically come from a lower socio-economic background, which is associated with having a lower parental-education level, lower income, and consequently, limited resources for obtaining adequate nutrition, and for having stimulating didactic materials in their homes, as well as not being able to afford enrichment activities (sport, music, dance). Almost all of these disadvantage factors are considered to be associated with lower academic performance (Crane, 1996;LeFevre et al, 2009;Davis-Kean, 2005;Dooley, 2011, McNamara & Kendeou, 2011Thornton, 2018). Consistent with this finding, Mullis and colleagues (Mullis et al, 2012) reported that a location of school (urban vs. rural) had a substantial impact on students' overall low mathematics achievement in the developing countries which are in close distance with Kosovo such as, Macedonia, Croatia, Romania, Turkey, etc.…”
Section: Discussionmentioning
confidence: 90%
“…Algunas prácticas que se pueden considerar de éxito para la inclusión educativa en zonas rurales coinciden en manifestar el alto compromiso de los orientadores escolares y sus habilidades comunicativas, sus competencias para asesorar al profesorado ante situaciones imprevistas y, entre otras cuestiones, las estrategias que emplean para procurar una mejor inserción socio-laboral del alumnado más vulnerable (Ritacco, 2011). De igual forma, una experiencia con alumnos con diversidades conductuales y emocionales en zonas rurales recoge algunas claves desarrolladas por los orientadores con un impacto positivo en su inclusión socio-educativa en el marco de las corrientes de la psicología positiva, como son el asesoramiento individualizado para desarrollar nuevas habilidades que faciliten sobrevenirse a los problemas (Thornton, 2018).…”
Section: El Papel Del Orientador Escolar En Entornos Ruralesunclassified